Treatment and Standards of Care for Cataract and Refractive Surgery in Germany during 2018: A Metadata Approach - Christian Schäferhoff; Jörg Förster; Bernd Schneider (Advanced Concepts in Medicine and Medical Research Vol. 10, 2023)
This chapter highlights to improve the treatment and standards of care for cataract and refractive surgery in Germany and to offer a tool for benchmarking through the establishment of a reference database in Germany where surgeons could record and analyze their own outcomes. Cataract is the world’s leading eye disease that causes blindness. Standards for cataract surgery are developing worldwide. The revolution of cataract surgery has never stopped and has been going on, from early intracapsular cataract extraction (ICCE) via extracapsular cataract extraction (ECCE) to current phacoemulsification (PCS) and even femtolaser-assisted cataract surgery. The German registry for cataract surgery was established in 2014. The main aim of this registry was to improve cataract surgery outcomes. The Annual Report on Cataract Surgery Germany (ARCSG) started in 2014. Ophthalmic surgeons across Germany were invited to contribute data on their cataract surgeries. Data collection includes data in quality control and benchmark tools on preoperative, intraoperative and postoperative parameters. The analyzed data included parameters of surgical technique, implanted intraocular lens (IOL), refractive and visual outcomes. During the year of 2018, the German registry included 10,035 lens exchange surgeries and the complete follow-up was available for 9,882 lens extractions. Our data revealed a complete follow-up for 9,882 lens extractions. Visual and refractive outcomes are the ones that will allow comparing our results to other reported results as a measure of quality control. Approximately one third of the patients were between 76 and 80 years old and 60.6% of the cases had a best-corrected distance visual acuity (CDVA) before surgery of 0.5 or better. Parabulbar anesthesia was reported in 60.4% of the cases and phacoemulsification with implantation of a posterior chamber IOL was the chosen method in 92.2% of the cases. The power of the implanted IOL was between 21.0-22.9D in 29.4% of eyes. Surgical complications were reported in only 413 cases. After surgery, a CDVA of 0.5 or better was achieved in 90.8% of the cases. Most of the operated patients (64%) had a residual refractive error within ±0.5D (95% confidence interval 63.2–65.1). Our results show that the registry was implemented successfully with results comparable to the ones reported in EUREQUO. The enthusiasm for AI and machine learning is high, but one should bear in mind that the quality of the data output fully depends on the quality of data input and the proper data processing. This involves expertise, manpower and considerable costs.